Assessment of prescription completeness and antibiotic consumption at a rural health and training centre, Delhi - Kumar, Arvind; Bahl, Arti; Gupta, Sunil; Singh, Charan; Jain, Sudhir Kumar; Singh, Sujeet Kumar (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The prescription audit is a useful method to assess the doctors’ contribution to the rational use of drugs in a country. A prescription is considered complete when it covers all the parts of the prescription. The polypharmacy increased the risk of drug interaction, dispensing errors and confused the patients for dosage schedules. A prescription with the minimum number of drugs per prescription helps in rational pharmacotherapeutics. The objectives of this study were to describe the pattern and completeness of prescription at rural health and training center and to estimate antibiotic consumption at rural health and training center. Methods: A descriptive cross-sectional study was conducted to determine the current prescribing practice at RHTC. Data were collected in the two pharmacies of the rural hospital. A total of 612 prescriptions with the last refill were considered for the assessment. Results: The average number of drugs prescribed per prescription 3.53. The percentage of prescriptions in which an antibiotic was prescribed was 20%. The percentage of drugs prescribed by generic name and from an essential drug list was 71.5% and 98.7% respectively. The most commonly prescribed form of antibiotics was extended-spectrum penicillin. Conclusions: All the prescriptions were complete covered parts of prescriptions. The dosing errors were present in maximum prescriptions. The WHO prescribing indicators were within the limits, an average number of drugs per prescription suggests a practice of polypharmacy. The peak of the use of antibiotics was observed in September followed by January and November. The least use of antibiotics was in December followed by June.